Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$$f(m,n) = (2m+n, m+2n)$$

What do we have to do to find the inverse of this function?

I don't even know where to begin.

share|cite|improve this question
Do you know about matrices? – Julian Kuelshammer Oct 25 '12 at 21:36
do i have to find the inverse (matrice)? – Gladstone Asder Oct 25 '12 at 21:38
up vote 9 down vote accepted

Denote $$\begin{cases} u=2m+n,\\ v=m+2n. \end{cases}$$ To find inverse mapping is sufficient solve this system w.r.t variables $m$ and $n$: $$\begin{cases} 2u-v=3m,\\ 2v-u=3n. \end{cases}$$ From there $$\begin{cases} m=\frac{2u-v}{3},\\ n=\frac{2v-u}{3}. \end{cases}$$ Then $f^{-1}(u,\ v)=\left(\dfrac{2u-v}{3}, \ \dfrac{2v-u}{3} \right).$

share|cite|improve this answer

I think this might be a useful place to begin: We can invert a function $f$ of a single variable by solving the equation $f(x)=y$ for $x$. For example, we invert $f(x)=2x+1$ by solving the equation $2x+1=y$ to get $x=(y-1)/2$. We can then write $x=f^{-1}(y)=(y-1)/2$, where $f^{-1}$ is the inverse required.

In your case, you need to do the 2-variable equivalent: solve the equation $f(m,n)=(2m+n,m+2n)=(a,b)$ to get the input $(m,n)$ - which plays the role of $x$ - in terms of $(a,b)$ - which plays the role of $y$. Your answer should have the form $(m,n)=f^{-1}(a,b) = (\hbox{an expression in $a$ and $b$}, \hbox{another expression in $a$ and $b$})$.

share|cite|improve this answer
I dont understand the answer, all you have shown is the inverse f(u,v) but the question is asking for the inverse of f(m,n). – user76711 May 7 '13 at 22:16

The following is a solution with matrices: $f$ can be regarded as a linear function, e.g. $\mathbb{Q}^2\to \mathbb{Q}^2$. With respect to the standard basis this is given by the matrix $$\begin{pmatrix}2&1\\1&2\end{pmatrix}$$ Now you can invert this matrix. There are different methods for that. I'm just using the explicit formula given by Cramer's rule. The inverse is $$\frac{1}{3}\begin{pmatrix}2&-1\\-1&2\end{pmatrix}$$ Now you can interpret this as a linear function again and get $f^{-1}(m,n)=\left(\frac{2m-n}{3},\frac{-m+2n}{3}\right)$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.